Towards an Understanding of Circatidal Clocks - Rock, Alberto; Wilcockson, David; Last, Kim S. (Frontiers in Physiology, 2022)
Circadian clocks are an intrinsic element of life that orchestrate appropriately timed daily physiological and behavioural rhythms entrained to the solar cycle, thereby conferring increased fitness. However, it is thought that the first archaic ‘proto-clocks’ evolved in ancient cyanobacteria in a marine environment where the dominant time cues (zeitgebers) probably would have been lunar-driven and included tidal cycles. To date, non-circadian ‘marine clocks’ have been described with circatidal (~12.4h), circasemilunar (~14.8d), and circalunar (~29.5d) periodicity, mostly studied in accessible but temporally complex intertidal habitats. In contrast to the well described circadian clock, their molecular machinery is poorly understood, and fundamental mechanisms remain unclear. We propose that a multi-species approach is the most apposite strategy to resolve the divergence that arose from non-circadian clockwork forged in an evolutionary environment with multiple Zeitgebers. We review circatidal clock models with a focus on intertidal organisms, for which robust behavioural, physiological, or genetic underpinnings have been explicated, and discuss their relative experimental merits. Developing a comprehensive mechanistic understanding of circatidal clocks should be a priority because it will ultimately contribute to a more holistic understanding of the origins and evolution of chronobiology itself.